AlGaN/GaN Metal Oxide Semiconductor High-Electron Mobility Transistors with Annealed TiO2 as Passivation and Dielectric Layers - Yu-Shyan Lin; Chi-Che Lu (Micromachines, 2023)
This paper reports on improved AlGaN/GaN metal oxide semiconductor high-electron mobility transistors (MOS-HEMTs). TiO2 is used to form the dielectric and passivation layers. The TiO2 film is characterized using X-ray photoemission spectroscopy (XPS), Raman spectroscopy, and transmission electron microscopy (TEM). The quality of the gate oxide is improved by annealing at 300 °C in N2. Experimental results indicate that the annealed MOS structure effectively reduces the gate leakage current. The high performance of the annealed MOS-HEMTs and their stable operation at elevated temperatures up to 450 K is demonstrated. Furthermore, annealing improves their output power characteristics.